English Premier League manager perceptions of video assistant referee (VAR) decisions during the 2019-2020 season - Chen, R.; Davidson, N. P. (Soccer & Society, 2022)
Video Assistant Referee (VAR) has become an emerging component of soccer. Prior inquiries have explored its impact on various game-related foci, but there remains a research gap surrounding participant and manager reactions to its usage. In an effort to provide such insights, this study examines the manager reaction to every VAR decision of the 2019-2020 English Premier League (EPL) season, its inaugural year of use within the league. While the EPL indicated the decision to adopt VAR was intended to aide in increasing fairness within the sport, there remained questions as to whether managers would perceive these indications as reality. Using secondary sourced post-match comment interviews of managers, reactions to VAR decisions were coded and themed. Results indicate mixed themes of manager perceptions of VAR decisions in the EPL during its inaugural year. The implication of this study provides insight to managers` perceptions of an emerging component of soccer.